Comparação entre diferentes estratégias de melhoria visando à redução do lead time - Utiyama, Marcel Heimar Ribeiro (2016)
The focus in time is the cornerstone of modern manufacturing management approaches; among them the Time Based Competition (TBC) and the Quick Response Manufacturing (QRM). Lead time reduction brings significant gains which are obtained by means of improvements in the shop floor variables. To make improvements in these variables, managers need to choose the best way to invest his limited financial resources. This work look for the best strategy regarding the improvement in time to repair, time between failures and setup time: To perform improvements focused on mean, variability or eliminate the worst cases. The main focus of this work is the worst case strategy, it means, to find the situations in which this strategy is the best option. To perform this comparison a modeling/simulation was conducted and the three variables addressed in this work were modeled using the normal and lognormal probability distributions. Results show that for situations with moderate and high variability the worst case strategy is the best improvement option. We believe this strategy can bring significant benefits and it is probably less costly and easier to implement. For low variability situations we find that the mean strategy is the best option. In addition for this case, for two variables (time to repair and setup time) the worst case strategy is a good alternative for situations which it is not possible to reduce the mean of these variables. For the time to failure, the only good option remains the mean strategy.